Collective action and the intensification of cattle-feeding techniques: a village case study in Kenya's coast province - Swallow, Kimberly A. (International Food Policy Research Institute, 2000)
The adoption of intensified cattle-feeding techniques by smallholders in Sub-Saharan Africa has been slower than anticipated. This study seeks to better define and understand the role of local collective action in conditioning the strategies that smallholders choose to intensify their cattle-feeding techniques. Collective action was analyzed as a determinant of the transaction costs of accessing feed for these techniques. An in-depth case-study method was used in a single peri-urban village that was at a low-but-increasing level of intensification of land use. The research found that cattle-keepers were intensifying their cattle-feeding techniques, but in a much more marginal, step-wise fashion than anticipated. The process of intensification involved changes in transaction costs, which were born differently by smallholders depending on their sources of wealth and personal networks. Whereas pervious studies have found wealth to be a key factor conditioning the adoptability of new techniques, this study shows that personal networks can be used in some cases as a substitute for wealth.